Variation in rotavirus vaccination coding in state US Medicaid data. Issue 22 (16th May 2019) - Layton, J. Bradley; Butler, Anne M.; Brookhart, M. Alan; Panozzo, Catherine A.
Abstract: Differences in state Medicaid policies and practices may result in variation in the recording of individual-level vaccination claims, which may present challenges for vaccination research using state Medicaid data. We describe differences in procedure coding for rotavirus vaccination in four states' Medicaid programs by identifying rotavirus vaccine–specific codes and oral vaccine administration codes. The proportion of vaccinated children with vaccine-specific and oral vaccine administration codes differed substantially across states: two states used vaccine-specific codes almost exclusively (95.9% and 99.0%); one had exclusively oral vaccine administration codes (>99.9%); another had a mixture (32.1% vaccine-specific codes, 40.0% oral vaccine administration codes, and 27.9% both). Depending on the research question, studies using Medicaid data in states without (or with incomplete) vaccine-specific coding may be infeasible. Prior to initiating research, investigators should carefully evaluate state Medicaid policies and patterns of vaccination uptake, as vaccine reimbursement policies and availability of vaccine claims may vary.